ANALISIS PENGARUH CAPITAL ADEQUACY RATIO, RETURN ON ASSET, NON PERFORMING LOAN DAN SUKU BUNGA SBI TERHADAP JUMLAH KREDIT YANG DISALURKAN BANK (Studi pada Bank Umum Swasta Nasional Devisa yang terdaftar di BEI Periode 2010-2011) - Rahayu, Yoseva Maria Puji (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Return On Asset (ROA), Non Performing Loan, and Interest Rateof SBI on total outstanding of loans (Studies in Foreign Exchange Banks that listed in BEI over period 2010-2011). Types of research used in this research is explanative research that aims to explain the causal relationship between the causal variables through hypothesis testing. The sampling technique used was nonprobability sampling and obtained a sample of 21 companies and 42 samples in total. To test the hypothesis proposed in this study used regression analysis. Regression analysis showed that ROA, and CAR as well as have a significant influence on dividend policy, meanwhile DER and Firm Size have not a significant influence on total outstanding loans. Based on these results, banks can make Capital Adequacy Ratio, and Return On Asset as reference in predicting total outstanding of loans.. Keywords: Capital Adequacy Ratio (CAR), Return On Asset (ROA), Non Performing Loan (NPL), Interest Rate of SBI, total outstanding of loans